A study of the impact of inhibitors of DNA binding‐1 on proliferation and migration in human colon carcinoma cells. Issue 4 (19th March 2019) - Wu, Xue‐Liang; Wang, Li‐Kun; Xue, Jun; Dai, Yong‐Jun; Yang, Dong‐Dong; Qu, Ming; Guo, Fei; Han, Lei; Sun, Guang‐Yuan
Abstract : This study aims to explore the effect of an inhibitor of DNA binding‐1 (Id‐1) on the proliferation and migration of human colon carcinoma cell line SW480 and HT‐29. SW480 and HT‐29 cells transfected with Id‐1‐interference sequence were assigned to the experimental groups (inhibition groups 1 and 2), and SW480 and HT‐29 cells with blank interference sequence (blank groups) and blank load transfection (blank load groups) were assigned as the control groups. The expression of Id‐1 in six groups was detected by reverse transcription‐polymerase chain reaction (RT‐PCR) and Western blot. Cell proliferation in vitro was assessed by MTT assay. RT‐PCR and Western blot results demonstrated that the mRNA and protein expressions of Id‐1 in the inhibition group 1 were lower than those in the blank group 1 and blank load group 1. RT‐PCR and Western blot results revealed that the mRNA and protein expressions of Id‐1 were lower in the inhibition group 2 than in the blank group 2 and blank load group 2. The results of the growth curve revealed that proliferation ability was significantly weaker from the third day in the inhibition groups 1 and 2 than in the blank group and blank load group. Transwell chamber experiment and Matrigel invasion assay revealed that the number of Transwell cells significantly decreased in the inhibition groups 1 and 2 than in the blank groups and blank load groups ( P < 0.01). Id‐1 significantly promotes the proliferation and migration of human colon carcinoma cell lines SW480 and HT‐29.